Body Satisfaction, Weight Gain, and Binge Eating Among Overweight Adolescent Girls - Sonneville, Kendrin R. (2012)
OBJECTIVE: To examine if body satisfaction is associated with body mass index (BMI) change and whether it protects against the development of frequent binge eating among overweight and obese adolescent girls. METHODS: We used prospective data from 9 waves of an ongoing cohort study of adolescents, the Growing Up Today Study. At enrollment in 1996, participants were 9 to 14 years old. Questionnaires were mailed to participants annually until 2001, then biennially through 2007. Girls who were overweight or obese in 1996 were included in the analysis (n=1 559). Our outcomes were annual change in BMI and incident frequent binge eating, defined as binge eating at least weekly and no use of compensatory behaviors. RESULTS: At baseline, 57.2% of the overweight and obese girls were at least somewhat satisfied with their bodies. During 11 years of follow-up, 9.5% (95% confidence interval (CI) [7.8, 10.8]) of the girls started to binge eat frequently. Controlling for BMI and other confounders, overweight and obese girls who reported being at least somewhat satisfied with their bodies made smaller BMI gains (β=−0.10 kg/m(2), 95% CI [−0.19, −0.02]) and had 61% lower odds of starting to binge eat frequently (odds ratio (OR)=0.39, 95% CI [0.24, 0.64]) than their less satisfied peers. Compared to girls who were the least satisfied with their bodies, girls who were the most satisfied had 85% lower odds of starting to binge eat frequently (OR=0.15, 95% CI [0.06, 0.37]). The association between body satisfaction and starting to binge eat frequently was stronger for younger adolescents than older adolescents. CONCLUSIONS: While body dissatisfaction is common among overweight and obese girls, body satisfaction may protect against excessive weight gain and binge eating. Prevention of body dissatisfaction must begin early and should be considered as a component of both obesity and eating disorder prevention programs.